2001
DOI: 10.1097/00007890-200104270-00002
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Rats Transplanted With Adult Porcine Islets and Immunosuppressed With Cyclosporine A, Mycophenolate Mofetil, and Leflunomide Remain Normoglycemic for Up to 100 Days1

Abstract: Well-functioning APIs can be isolated in large numbers. API xenografts can be protected from rejection and can maintain an adequate function for up to 100 days, in rats immunosuppressed with CsA+MMF+LEF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 69 publications
2
13
0
Order By: Relevance
“…with earlier reports (29,32), and led to our standard dose of 15,000-30,000 IE/kg. However, transplanting an ex- One recipient had returned to hyperglycemia on day 8 after two consecutive blood glucose measurements of ≥20 mM/L (dotted line).…”
Section: Immunosuppression Recipient Ratssupporting
confidence: 88%
See 4 more Smart Citations
“…with earlier reports (29,32), and led to our standard dose of 15,000-30,000 IE/kg. However, transplanting an ex- One recipient had returned to hyperglycemia on day 8 after two consecutive blood glucose measurements of ≥20 mM/L (dotted line).…”
Section: Immunosuppression Recipient Ratssupporting
confidence: 88%
“…Recalculated on a per day baa good quality graft, especially of porcine islets, have in many instances contributed substantially. Apart from a sis, rats in the present study received ±6.5 mg/kg/day, which is less than half of the dose in the Swedish studies series of sparsely documented studies (13,20,30), two recent articles reported successful transplantation of (15 mg/kg/day) in which additionally substantial dosages of MMF and leflunomide (32) or FTY720 (21) adult porcine islets in the rat (21,32). In both studies the graft survivals were alike and remarkably similar to the were given daily.…”
Section: Immunosuppression Recipient Ratsmentioning
confidence: 79%
See 3 more Smart Citations